Determination of Trace Elements Content in Mineral Water and its Processed Mineral Water by ICP-MS - Rui, Yukui; Zhang, Yanbei; Li, Shengliang (Asian Journal of Chemistry, 2013)
Good natural mineral water has become important strategic resource. The macro and trace elements and five heavy metals were determined in natural mineral water from Emei mountain of Beijing and its processed mineral water by ICP-MS. The results showed that (1) natural mineral water contained many macro elements, especially Ca, Mg, Si Na and K, and the processing course did not significantly reduce the concentration of these elements; (2) natural mineral water contained much trace elements, including Li, Zn, Sr, Se, Mn, Cu and Fe, especially Sr, Fe and Se, and after processing, many trace elements increased significantly, such as Zn, Li and Se; (3) the natural mineral water from Emei mountain of Beijing and its processed mineral water contain much little heavy metals. By contrast with the national standards, the natural mineral water from Emei mountain of Beijing is excellent mineral water and its processed mineral water also meet the national hygiene standards of drinking water.